Srebrenica 360° - Kipfer, Conny (Switzerland : Cadrage Gmbh, 2009)
The east Bosnian town of Srebrenica came to sad prominence in 1995: Serbian nationalists murdered 8000 Muslim men and boys during the Bosnian war. The genocide is still present: The women are missing their husbands, their brothers, their fathers, their sons. In this film people from Srebrenica get a chance to speak. They talk about their hard life, about unemployment, about the hope for a peaceful coexistence and the longing for justice.
Verzio Film Festival Submission
Duration: 00:56:00
Verzio Film Festival Submission
Keywords: Documentary films